The effects of defensive footwork on the kinematics of Taekwondo roundhouse kicks - Jung, T.; Park, H. (European Journal of Human Movement, 2018)
The roundhouse kick is the most frequently used in Taekwondo sparring matches. In order to execute the kicks, footwork techniques are critical, especially for players` counterattack. Therefore, the purpose of this study was to biomechanically examine the effects of different defensive footwork on the Taekwondo roundhouse kicks. Ten male university elite Taekwondo athletes executed roundhouse kicks with seven back-step conditions The duration of the phases of the kick, the center of mass displacement, trunk angle, left-foot-axis-angle, and kicking foot velocity were obtained through a three-dimensional video motion analysis. These variables were compared to the conditions using repeated measure analysis of variance, and they changed significantly in response to different back-step conditions. It was concluded that the most effective back-step angle for defense and attack was 2/3 of 90° between the x- and y-axes. Also, as the one-step-back-step`s angle increases, foot velocity could be increased; on the contrary, when the one-step-back-step`s angle was reduced, the Taekwondo athlete could execute a fast counterattack, but it could be exposed to the opponent's attack. Therefore, it would be necessary to make efforts to compensate for the strengths and weaknesses of the types of back-step techniques so as to avoid the opponent's attack.